2017
DOI: 10.4254/wjh.v9.i26.1081
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion weighted magnetic resonance imaging of liver: Principles, clinical applications and recent updates

Abstract: Diffusion-weighted imaging (DWI), a functional imaging technique exploiting the Brownian motion of water molecules, is increasingly shown to have value in various oncological and non-oncological applications. Factors such as the ease of acquisition and ability to obtain functional information in the absence of intravenous contrast, especially in patients with abnormal renal function, have contributed to the growing interest in exploring clinical applications of DWI. In the liver, DWI demonstrates a gamut of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 101 publications
1
40
1
1
Order By: Relevance
“…In the viewpoint of feature analysis in image processing, ADC is a voxel‐based feature that uses voxel intensities of the ADC map as features in classification. Although it is very simple to use and is intuitive to interpret clinical results, previous studies have reported conflicting results using the ADC value to estimate the pathological grade of HCC . This conflict of reported results may be due to the overlap in the ADC values of different malignant HCCs, while another possible reason is that ADC measurements may result from calculation errors as they are very sensitive to motion and artifacts in DWI, which remarkably decreases the performance of ADC measurement for lesion characterization .…”
Section: Introductionmentioning
confidence: 99%
“…In the viewpoint of feature analysis in image processing, ADC is a voxel‐based feature that uses voxel intensities of the ADC map as features in classification. Although it is very simple to use and is intuitive to interpret clinical results, previous studies have reported conflicting results using the ADC value to estimate the pathological grade of HCC . This conflict of reported results may be due to the overlap in the ADC values of different malignant HCCs, while another possible reason is that ADC measurements may result from calculation errors as they are very sensitive to motion and artifacts in DWI, which remarkably decreases the performance of ADC measurement for lesion characterization .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DWI imaging is susceptible to artifacts (e.g., blurring, ghosting, and distortions) and offers a limited image quality; therefore, DWI is currently used as complementary and not as a replacement to conventional sequences in the evaluation of NAFLD [47].…”
Section: Diffusion-weighted Mr Imagingmentioning
confidence: 99%
“…DWI does not require administration of intravenous contrast; consequently the technique might represent a reasonable option for patients with kidney failure, where gadolinium-based contrast substances represent a contraindication due to the increased risk of developing nephrogenic systemic fibrosis, while iodinated CT contrast might lead to an even greater impairment of renal function, being also contraindicated [47].…”
Section: Diffusion-weighted Mr Imagingmentioning
confidence: 99%
“…Данная методика практически не приводит к удлинению времени выполнения МРТ и легка в применении [42]. Из недостатков ДВИ отмечают низкую воспроизводимость значений ИКД из-за отсутствия стандартизации методики, а также высокую чувствительность к артефактам [29,34]. МР-перфузия является новейшей методикой, позволяющей по аналогии с КТ-перфузией не только диагностировать морфологические изменения, но и определять функциональные параметры органов и тканей.…”
Section: компьютерная томографияunclassified